Cytological study of body fluids for malignancy - Dr. Husain Saba; Dr. Prakash C.J.; Dr. Sharmila P.S; Dr. Vinitra. K. (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: The effusion fluid analysis plays an important role in neoplastic conditions. The present study was undertaken to highlight the frequency of malignant cells in various body fluid. Materials and Methods: This observational study was performed for the period of one and half year. A total of 250 various type of body fluid samples received during the study period in the Department of Pathology, Rajarajeshwari Medical College and Hospital, Bengaluru, Karnataka were studied. Results: Most of the fluid samples belonged to males (59.20%) and the male to female ratio was 1.45:1. The common age group of specimen received was 40 to 50 years (21.20%). Most of the malignant lesions that is 53.85% and most of the suspicious of malignancy that is 66.67% were belonged to peritoneal fluid. Conclusions: Pleural fluids were the most common type of fluid received for analysis. Most of the fluid samples belonged to males. The frequency of malignancy in the population studies was 5.20% with adenocarcinoma being the common malignant lesion.